2020
DOI: 10.1136/jmedgenet-2020-107503
|View full text |Cite
|
Sign up to set email alerts
|

Adopted individuals’ interest in elective genomic testing

Abstract: PurposeAdoptees are a population that could benefit from genetic testing to fill gaps in family health history (FHH). Elective genomic testing (EGT) provides adoptees with clinical genetic testing options to learn about genetic health risks in the absence of FHH. We assessed adoptees’ interests in, motivations for and perceived utility of EGT.MethodsAdult adoptees and non-adoptees completed an anonymous, online survey regarding their interest and motivations for EGT, perceived utility of potential results and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Three studies conducted focus groups [ 53 , 55 , 60 ] while one study used both focus groups and a survey [ 58 ]. The US has contributed the most to this field thus far, undertaking six of the 16 studies identified in the literature search [ 49 , 50 , 52 , 53 , 55 , 58 ]. This is followed by Canada ( n = 2) [ 48 , 51 ] and Japan ( n = 2) [ 54 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies conducted focus groups [ 53 , 55 , 60 ] while one study used both focus groups and a survey [ 58 ]. The US has contributed the most to this field thus far, undertaking six of the 16 studies identified in the literature search [ 49 , 50 , 52 , 53 , 55 , 58 ]. This is followed by Canada ( n = 2) [ 48 , 51 ] and Japan ( n = 2) [ 54 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“… Not representative Survey with questions regarding respondent demographics, interest in whole genome sequencing for themselves and their youngest children. Edgar et al [ 50 ] USA To have a better understanding of the specific genomic risk information adoptees are interested in learning. Total = 341; Non-adoptees = 229; Adopted individuals = 112 Non-adopted individuals were recruited via Amazon Mechanical Turk, a crowdsourcing Internet platform.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our participants also varied widely in their views about the desirability of communicating with previously unknown relatives. As has been observed by others, some were eager to find kin, especially those who had few relatives or gaps in their family history [ 45 ] or who had been adopted [ 55 ]. Many, however, expressed concerns about intrusion on their personal privacy, being taken advantage of, and potential to upset existing family relationships and to create new obligations [ 28 ].…”
Section: Discussionmentioning
confidence: 95%